0120 Cleaning tasks and respiratory, dermatological and musculoskeletal symptoms among custodians using traditional and green cleaners. (23rd June 2014) - Cavallari, Jennifer; Bruno Garza, Jennifer; Wakai, Sara; Simcox, Nancy; Schenck, Paula; Welsh, Loyola; Meyer, John; Morse, Tim; Cherniack, Martin
Abstract : Objectives: As part of a larger study investigating the transition from traditional to green cleaners, we sought to investigate the relationships between cleaning tasks and respiratory, dermatological and musculoskeletal symptoms among a population of custodians. Method: State-employed custodians completed a questionnaire to assess cleaning tasks and health symptoms using standardised questions when available. Associations between health outcomes and cleaning tasks were investigated using logistic regression after controlling for age, gender, and smoking status. Each health outcome was modelled individually and trends with increasing exposures are reported. Results: Questionnaires were completed by 329 custodians from three universities and one university health centre. Participants were 59% female, 53% reported English as their primary language, and 18% were current smokers. Health symptoms within the last month included dermatitis (26%), lower-respiratory complaints (30%), upper-respiratory complaints (43%), pain or discomfort in back (32%) and pain or discomfort in neck, shoulders or arms (44%). An increasing number of toilets cleaned was associated with increased odds of dermatitis (p for trend =0.0005), lower-respiratory symptoms (p = 0.007), and pain or discomfort in shoulders (p = 0.04). Increasing daily hours spent floor stripping was associated with increased odds of dermatitis (p = 0.02), lower- (p = 0.01) and upper- (p = 0.01) respiratory symptoms as well as pain or discomfort in back (p = 0.006). Increasing daily hours of vacuuming was associated with increased odds of lower- (p = 0.03) and upper- (0.003) respiratory symptoms. Conclusions: Custodian dermatological, respiratory, and musculoskeletal symptoms are consistent with task related exposures and follow a dose-related pattern with increasing odds of symptoms related to increased exposure duration.